Determinant factors of under-five years severely wasted children in rural and sub-urban areas of Indonesia - Erma Sulistyaningsih; Endang S. P. Wulandari; Ancah C. N. Marchianti (Wolters Kluwer Medknow Publications, 2024)
Background: Understanding the determinant factors contributing to severely wasted is crucial in decreasing the problem and meeting the World Health Global Nutrition Target by 2025. This study investigated the determinants of severely wasted among children under five years old in Indonesia's rural and sub-urban areas. Materials and Method: This was a cross-sectional study of severely wasted children in rural and sub-urban areas in East Java, Indonesia. Collected data on individual characteristics, socio-economic status, nutrient intake, environmental and food sanitation, and health service utilization were obtained by structured questionnaires. An ordinal regression and Chi-square test were applied to determine the factors with a significance level 0.05. Results: As many as 25 respondents in rural areas and 30 in sub-urban areas were included after receiving informed consent. Age and household environmental and food sanitation were associated with severely wasted in rural and sub-urban areas, with P < 0.05. Meanwhile, family members, income, and calcium intake were only in rural areas. Birth spacing, nutrient intake, except calcium intake, and health care utilization were the only factors in sub-urban areas. The low-birth-weight history, sex, mother's education, and the parent's occupation did not correlate with the severely wasted in rural and sub-urban areas. Conclusion: The determinant factors of under-five years of severely wasted children in rural and sub-urban areas of Indonesia are different, so it is vital to design regional-based approaches to tackle the problem.